2002
DOI: 10.1067/mtc.2002.122551
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation, fibrinolysis, and cell activation in patients and shed mediastinal blood during coronary artery bypass grafting with a new heparin-coated surface

Abstract: The Corline Heparin Surface used in cardiopulmonary bypass proved to be more biocompatible than an uncoated surface when using a standard systemic heparin dose. The low dose of systemic heparin might not be sufficient to maintain the antithrombotic activity, and the high dose resulted in direct cell activation rather than a further anti-inflammatory and anticoagulatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 43 publications
(64 reference statements)
0
41
0
8
Order By: Relevance
“…Studies have shown lower fi brinopeptide A [87], tPA, tPA antigen, prothrombin activator peptide [88,89] and TAT levels [52], indicating both decreased coagulation and fi brinolysis. Heparin bonded circuits, along with improving pulmonary function, also decreased complement activation in pediatric patients resulting in improved coagulation after surgery as evidenced by lower prothrombin time [90].…”
Section: Antifibrinolytic Agentsmentioning
confidence: 97%
“…Studies have shown lower fi brinopeptide A [87], tPA, tPA antigen, prothrombin activator peptide [88,89] and TAT levels [52], indicating both decreased coagulation and fi brinolysis. Heparin bonded circuits, along with improving pulmonary function, also decreased complement activation in pediatric patients resulting in improved coagulation after surgery as evidenced by lower prothrombin time [90].…”
Section: Antifibrinolytic Agentsmentioning
confidence: 97%
“…Because the outer side of the PMEA molecule is chemically inert, its surface has little tendency to react with blood components [ 48 ] . ROCSafe (Terumo) circuit is completely covered with a PMEA coating [ 33 ] Reduced activation of platelets [ 34 ] Reduced activation of the complement system [ 35 ] Limitation of cytokine release [ 36 ] Reduced kallikrein/kinin complex activation [ 37 ] Reduced stimulation of the coagulation system [ 38 ] Suppression of tissue plasminogen activator (tPA) release [ 39 ] Reduced plasmin-antiplasmin complex (PAP) levels [ 40 ] to minimize the adsorption and denaturation of proteins and blood cells during extracorporeal circulation [ 49 ] . Circular dichroism spectroscopy revealed that low-platelet adhesion and spreading are closely related to the low degree of the denaturation of the protein adsorbed onto PMEA.…”
Section: Tubingmentioning
confidence: 99%
“…16 Modifications of the blood salvage procedure (avoiding the re-infusion of shed mediastinal blood, or return after washing and centrifugation via a cell-saving device) or the use of heparin-bound circuits could limit blood activation and reduce the amount of heparin required. [17][18][19][20][21] The ACT values obtained by different monitors or with different activators cannot be interchanged, particularly during anticoagulation with heparin. 22 A comparative study in patients undergoing percutaneous coronary angioplasty showed that the results of the ACT II® were 130 sec shorter than those of the Hemochron® ACT.…”
Section: S90mentioning
confidence: 99%